Thrombospondins in human aortic aneurysms. Issue 10 (16th March 2022) - Plana, Emma; Oto, Julia; Medina, Pilar; Herranz, Raquel; Fernández‐Pardo, Álvaro; Requejo, Lucia; Miralles, Manuel
Abstract: Thrombospondins are a family of matricellular proteins with a multimeric structure that is known to be involved in several biological and pathological processes. Their relationship with vascular disorders has raised special interest recently. Aortic aneurysms are related to the impairment of vascular remodeling, in which extracellular matrix proteins seem to play an important role. Thus, research in thrombospondins, and their potential role in aneurysm development is progressively gaining importance. Nevertheless, studies showing thrombospondin dysregulation in human samples are still scarce. Although studies performed in vitro and in vivo models are essential to understand the molecular mechanisms and pathways underlying the disorder, descriptive studies in human samples are also necessary to ascertain their real value as biomarkers and/or novel therapeutic targets. The present article reviews the latest findings regarding the role of thrombospondins in aortic aneurysm development, paying particular attention to the studies performed in human samples.